An EOQ Model with Partial Backorder for Fuzzy Demand and Learning in Fuzziness - Suthar, Shivangi N; Soni, Hardik N (International Journal of Computer Sciences and Engineering, 2018)
This study demonstrates an EOQ model with partial backorders over the finite time horizon assuming imprecise demand which is characterized by triangular fuzzy number. Learning effect is considered to reduce the impreciseness of demand as inventory planners get experienced by collecting knowledge from previous cycles. This paper aims to find out the optimal number of replenishments and an optimal fraction of the cycle during the positive inventory to minimize the total annual cost. The optimal policy is derived using analytical approach for crisp and fuzzy model whereas algorithmic procedure is adopted for the fuzzy-learning model. To show the significance of learning effect, numerical analysis is executed and compared results from the crisp, fuzzy and fuzzy-learning case which shows that increasing human learning reduces fuzziness of the demand and approaches to the crisp model.